AHA CENTRE (ASEAN COORDINATING CENTRE FOR HUMANITARIAN ASSISTANCE ON DISASSTER MANAGEMENT) DALAM MENANGANI DAMPAK BENCANA TSUNAMI PALU TAHUN 2018 - Kaffi, Aliafu Al; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The tsunami that struck Palu on September 28, 2018 was one of the largest natural disasters ever to hit Indonesia. It not only caused significant physical and material losses, but also posed major challenges in emergency response and recovery efforts. In this context, the AHA Centre (ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management) played an important role in addressing the impact of the disaster as part of the ASEAN regional cooperation framework in the humanitarian field. This study aims to analyze the role of the ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management (AHA Centre) in dealing with the impact of the tsunami disaster in Palu in 2018. The research method used is qualitative with data collection techniques in the form of literature studies. The perspective used is liberalism, with the IGO theory, and the level of group analysis which explains how the inter-governmental organization group carries out its role, especially in the informational and operational functions of the tsunami disaster in Palu in 2018. The results of this study show that the role of the AHA Center in the 2018 Palu tsunami disaster response is one of the concrete implementations of ASEAN regional cooperation. However, further strengthening is still needed, especially in local capacity, so that member states can increase their self-reliance in dealing with emergency situations. Thus, the AHA Centre is not only a symbol of ASEAN solidarity, but also an important driving agent in accelerating disaster response and facilitating the recovery process for affected communities. Keywords: AHA Center, Tsunami, Palu, IG